Bifurcation for the solutions of equations involving set valued mappings - E. U. Tarafdar; H. B. Thompson (International Journal of Mathematics and Mathematical Sciences)
This paper is devoted to a generalization of the bifurcation theorem of Karsnosel'skii and Rabinowitz to the set valued situation.